Navigating young motherhood: a retrospective study into the reflections of the teenage motherhood experience by mothers within a community of the Western Cape - Boshoff, Sinead Madelyn (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA) -- Stellenbosch University, 2022.